Study of the Content of Somatic Cells in Cow’s Milk in Armenia - Balayan, E. B.; Araksyants, A. E. (ՀԱԱՀ հիմնադրամ)
The aim of the research is to understand the quality of milk and the state of animal health in Armenia, using the Somatic Cell Counts (SCC) as an indicator. As a result, we have received a clear map of milk quality in five regions of the Republic of Armenia, the data of which are extremely alarming. According to the SCC, 12 % of 135 animals have clinical mastitis, 23 % have developed mastitis and the remaining 65 % do not have mastitis. To improve the quality of milk and the state of animal health, we suggested that processing companies apply a financial scheme of incentives and penalties to suppliers.
Keywords: Veterinary Science and Animal Breeding